2018
DOI: 10.1038/s41598-018-26412-6
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic, environmental and lifestyle factors associated with gestational diabetes mellitus: A matched case-control study in Beijing, China

Abstract: Gestational diabetes mellitus (GDM) is a common health problem during pregnancy and its prevalence is increasing globally, especially in China. The aim of this study was to investigate socioeconomic, environmental and lifestyle factors associated with GDM in Chinese women. A matched pair case-control study was conducted with 276 GDM women and 276 non-GDM women in two hospitals in Beijing, China. Matched factors include age and pre-pregnancy body mass index (BMI). GDM subjects were defined based on the Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 50 publications
(56 reference statements)
0
44
0
1
Order By: Relevance
“…First, considerable controversies remain regarding the timing of GDM screening and diagnostic thresholds; independent studies with other diagnostic criteria should be performed to validate the findings of this study. Second, recent studies show that lifestyle is an important determinant of GDM development . Unfortunately, information regarding lifestyle factors was not collected in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, considerable controversies remain regarding the timing of GDM screening and diagnostic thresholds; independent studies with other diagnostic criteria should be performed to validate the findings of this study. Second, recent studies show that lifestyle is an important determinant of GDM development . Unfortunately, information regarding lifestyle factors was not collected in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Second, recent studies show that lifestyle is an important determinant of GDM development. 33,34 Unfortunately, information regarding lifestyle factors was not collected in this study. Third, the genotype-phenotype associations were based on a public database, and further confirmatory studies with detailed functional experiments are warranted to uncover the mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, advanced etiological studies have revealed GDM to be a multifactorial pregnancy disease which can be induced by genetic factors, insulin resistance (IR), inflammation and adipokine involvement (17). In a case-controlled study reporting GDM incidence, the prevalence of GDM in pregnant Chinese women was between 6.8-10.4%, with increased prevalence in the Beijing area at 19.7% (18).…”
Section: Discussionmentioning
confidence: 99%
“…First, the level ofplasma vitamin D was not measured in all subjects. Second, the information of environmental and lifestyle factors was lacked, which had been reported recently to be important determinants of GDM development [36,37] . Finally, there were some potential biases that came from the cross-sectional nature of the case-control study.…”
Section: Discussionmentioning
confidence: 99%